The departure : the owner, Book one - Asher, Neal L., 1961- (Asher, Neal L., 1961- Owner., 2013)
Visible in the night sky, the Argus Station, its twin smelting plants like glowing eyes, looks down on nightmare Earth. From Argus, the Committee keep an oppressive control: citizens are watched by cams systems and political officers, it's a world inhabited by shepherds, reader guns, razor birds and the brutal Inspectorate with its white tiled cells and pain inducers. Soon the Committee will have the power to edit human minds, but not yet, as twelve billion human beings need to die before Earth can be stabilized, but by turning large portions of Earth into concentration camps this is achievable, especially when the Argus satellite laser network comes fully online.